Effects of the Use of CDIO Engineering Design in a Flipped Programming Course on Flow Experience, Cognitive Load - Zhong, Hua-Xu; Chiu, Po-Sheng; Lai, Chin-Feng (Sustainability, 2021)
The flipped teaching method has become increasingly mature and critical. Previous flow experience studies have concentrated on game-based learning, and cognitive load studies have concentrated on different types of teaching materials (e.g., video). Due to the characteristic differences between problem-based learning and the Conceive, Design, Implement, Operate (CDIO) engineering design, the authors were interested in applying the CDIO engineering design to the flipped programming course. This study was proposed to measure students’ cognitive load and flow experience by using CDIO engineering design in the flipped programming course, which used a one-group pretest–post-test nonequivalent-groups design method for 16 weeks. This study recruited 40 college students (males = 14, females = 26) who were first-year freshmen attending a university as its subjects. The results indicate that the students showed no significant improvement between cognitive load and gender difference in cognitive load and flow experience, but that they significantly improved some dimensions of flow experience. This study provides implications and evidence related to applying the CDIO engineering design in flipped programming courses.